GENOMIC INSTABILITY AND LIPID PEROXIDATION IN PATIENTS WITH TREATED ESSENTIAL HYPERTENSION: Life Science-Medicine and Genetics - THUKRAL, KAPILA; GANDHI, GURSATEJ (International Journal of Life Science and Pharma Research, 2012)
Impaired oxidant/antioxidant status in hypertension results in increased oxidative stress. This may cause genomic instability, damage membrane proteins and lipid peroxidation in hypertensive individuals. Aim: The aim of this study was to assess genomic instability (DNA damage) and lipid peroxidation in treated hypertensive patients belonging to a population sub-group. Materials and Methods: A case-control study was carried out on amlodipine-atenolol treated hypertensive patients (n=22) and normotensive (n=10) control group, belonging to same sub-group. The study was approved by Institutional Ethics Committee. The demographic, physiometric, anthropometric variables were recoded after the written informed consent. The leukocyte DNA damage by the single cell gel electrophoresis assay and malondialdehyde (MDA) levels using standard protocols were assessed in the study group to investigate genetic damage and oxidative stress. The data was expressed as mean ± S.E.M. Chi-square, student’s t-test, ANOVA, Pearson correlation and multiple linear regression were used to compare and find association if any of the damage parameter with the confounding variables. Results: DNA damage was significantly elevated (p=0.003) in the hypertensive patients compared to value in normotensive individuals. MDA levels were also significantly increased in patients. Conclusion: The increased genetic damage and levels of lipid peroxidation in hypertensive patients were associated with the elevated blood pressure, abnormal lipid profile, obesity and drug treatment. The genomic instability probably resulted as a consequence of oxidative stress from these variables and drug treatment increase the risk for cardiovascular diseases, target-organ damage and carcinogenesis